Nghiên cứu quy trình tổng hợp febrifugine hydrochloride - Kim Phượng, Đỗ Thị; Mai Hương, Đoàn Thị; Nam, Vũ Văn; Hiệu, Trần Văn; Ngân, Trương Bích; Vinh, Lê Công; Cường, Phạm Văn; Hùng, Nguyễn Văn; Giang, Vo Châu; Minh, Châu Văn (Vietnam Journal of Chemistry, 2014)
Febrifugine, a quinazoline alkaloid, isolated from Dichroa febrifuga roots, shows powerful antimalarial activity against Plasmodium falciparum. Strong liver toxicity has precluded febrifugine as a potential clinical drug. However, the potent antimalarial activity of febrifugine has stimulated medicinal chemists to pursue compounds derived from febrifugine, which may be valuable leads for novel drugs. Total synthesis and structural modification of febrifugine have been made. Among the reported asymmetric approaches to febrifugine, one of the most straight forward approaches to construct the 2-substituted 3-hydroxy piperidine is the stereoselective reaction of 3-hydroxy-piperidine N-acyliminium ions with the nucleophiles. In this study, we synthesized febrifugine hydrochloride (13) from L-glutamic acid (1) base on the asymmetric BF3.Et2O catalyzed nucleophilic reactions. The precursor 12 was formed by open epoxy ring using triethylamine and then oxidation with Dess-Martin periodinane. Their structures were established by MS and NMR spectroscopies. Keywords: Febrifugine, antimalarial activity